Increase in driving after cocaine use in Spain: a cross-sectional dataset analysis for 2021 - García-Mingo, Mercedes; Martín-Fernández, Marta; Gutiérrez-Abejón, Eduardo; Álvarez, F. Javier (Frontiers in Public Health, 2023)
Objective: Driving under the influence of alcohol and/or drugs impairs skills essential for safe driving, increases the risk of being involved in a traffic accident and is particularly prevalent in Spain. To assess the prevalence of positive substance driving cases, what factors may be associated with driving after substance use, and the evolution of the presence of drugs in drivers from the 2008, 2013, 2018, and 2021 studies. Study Design and Setting: The present study was conducted in a representative sample of Spanish drivers in 2021 for alcohol (breath) and psychoactive substances (oral fluid (OF)). A total of 2980 drivers were included in this study: 76.53% were male with a mean age of 41.35 ± 13.34 years old. Results: In 2021, 9.29% of drivers tested positive for alcohol and/or drugs. Alcohol alone was found in 4.20% of cases, alcohol plus another substance in 0.32% of cases, one drug only in 4.41% of cases, and more than one type of drug other than alcohol in 0.37% of cases. Overall, cocaine cases were the highest registered in 2021 (2.42%), while cannabis (1.86%) and polydrug cases (0.69%) were the lowest, with respect to the 2008/2013/2018 studies. Conclusions: Data from the 2021 study show that the presence of substances found in nine out of 100 drivers remains unacceptably high in Spain, with a marked increase in the frequency of driving after cocaine use. Further interventions and measures must be taken to avoid driving under the influence of alcohol and/or drugs.